Răspunsuri

2014-05-03T22:11:19+03:00
X²+3x-4=x²+3x-3-1=x²-1+3(x-1)=(x-1)(x+1)+3(x-1)=(x-1)(x-4)⇒x1=1, x2=-4
x²-4x=21⇒x²-4x-21=0, Δ=100 x1=7, x2=-3
4(x+3)=(x+2)²⇒4x+12=x²+4x+4,x²-8=0, x1=2√2, x2=-2√2
(x-4)²=-x(x+20)+8(x-4),   x²-8x+16=-x²-20x+8x-32, 2x²+4x+48=0, x²+2x+24=0, Δ=4-4*24=4-96=-92 x1=(-2+2i√23)/2=-1+i√23, x2=-1-i√23     x1, x2∈C,C-multimea nr complexe
5x-15y+10z=5(x-3y+2z)

25x²*y²-15x³y+5xy²=5xy(5xy-3x²+y)
nu stiu ce se cere la acestea din urma, dar sper ca am inteles ceea ce s-a cerut